Vajdasági magyar pártok 1990 után - Mátyus, Ákos (Közép-Európai Közlemények, 2011)
My current study’s main focus concentrates on the political parties and organizations of Vojvodina (officially: Autonomous Province of Vojvodina), from their earliest movements –dating back to the events of the Eastern-European democratic transformations –to nowadays’ situation. To establish the topic I consider it quite important to emphasize and give a general view about the possibilities of advocation available during the reign of the previous regime as well as the main characteristics of the Southern Slavic minority politics. Beginning with the 1990s, in the northern territory of Serbia, we witnessed the formation of one of the most complex and complicated party relations existing in the Carpathian Basin between Hungarian parties, due to which the majority of the divided community turned away from the parties declaredly representing their interest. I will attempt to discuss the course events in a chronological order, exploring the reason and origin of the animosity lying between these organizations. Although the autocracy of Milošević had been abolished for over ten years, most of the original goals of these parties have not been met as of yet. Despite this, there is no prospect of cooperation among them, though the underlying cause is not an ideological one but the very reason of nearly two-decade-long individual oppositions.